2020
DOI: 10.1159/000511591
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Outcomes after 36-Month Treatment with Ranibizumab 0.5 mg in Patients with Visual Impairment due to Diabetic Macular Edema (BOREAL-DME)

Abstract: <b><i>Purpose:</i></b> To assess the efficacy, safety, and follow-up of 36-month treatment with ranibizumab in patients with diabetic macular edema (DME) in real-life setting. <b><i>Methods:</i></b> This is a prospective phase 4 observational study. Between December 2013 and April 2015, 84 ophthalmologists enrolled a total of 290 adult patients initiating ranibizumab for visual impairment due to DME and treated them according to their routine practice. The primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 21 publications
(31 reference statements)
0
13
0
3
Order By: Relevance
“…Massin reported mean BCVA gains of +4.1 letters after 36 months. 15 However, in this cohort, only half of the patients who completed the 36-month follow-up had been treated with ranibizumab only, the remaining patients switched to other intravitreal drugs. The ETOILE cohort had similar baseline BCVA and gains at M24, and similar numbers of injections.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Massin reported mean BCVA gains of +4.1 letters after 36 months. 15 However, in this cohort, only half of the patients who completed the 36-month follow-up had been treated with ranibizumab only, the remaining patients switched to other intravitreal drugs. The ETOILE cohort had similar baseline BCVA and gains at M24, and similar numbers of injections.…”
Section: Discussionmentioning
confidence: 95%
“…Under-treatment was also reported in another three-year French prospective real-world study of ranibizumab in DME that showed fewer visits (mean 13.4) and injections (mean 5.1) than recommended in year 1, decreasing further in subsequent two years. 15 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations